Tantangan dalam Perizinan Infrastruktur Ketenagalistrikan: Studi Kasus Pengembangan Gardu Induk di Sumatera Selatan - Junaedi, Junaedi; Saputro, Adi; Sami’an, S. (SIGn Jurnal Hukum, 2024)
Substation development plays a crucial role in supporting the enhancement of the electricity sector in Indonesia. However, the permitting process for such infrastructure development still faces several challenges. This research aims to analyze the determinant factors causing delays in permitting the Muara Enim 500 kV EHV Substation development in South Sumatra. Employing a juridical-empirical approach and a case study method, this research examines the applicable permitting regulations, namely Law Number 30 of 2009 and its implementing regulations. The results indicate that the permitting delays were caused by weak coordination among involved stakeholders, adjustments to four changes in permitting regulations during the project, and non-regulatory factors such as land acquisition and community engagement. To improve the permitting system, four strategic pillars are recommended: strengthening the regulatory framework through harmonization and simplification, accelerating the digitalization of the permitting process, enhancing human resource capacity, and strengthening cross-sectoral coordination complemented by active community engagement. Implementing this comprehensive strategy is expected to expedite substation development to support the sustainable growth and improvement of the electricity sector.